Genetic variability and heritability of chlorophyll a fluorescence parameters in Scots pine (Pinus sylvestris L.) - Čepl, Jaroslav; Holá, Dana; Stejskal, Jan; Korecký, Jiří; Kočová, Marie; Lhotáková, Zuzana; Tomášková, Ivana; Palovská, Markéta; Rothová, Olga; Whetten, Ross W; Kaňák, Jan; Albrechtová, Jana; et al. (Tree physiology, 2016)
Current knowledge of the genetic mechanisms underlying the inheritance of photosynthetic activity in forest trees is generally limited, yet it is essential both for various practical forestry purposes and for better understanding of broader evolutionary mechanisms. In this study, we investigated genetic variation underlying selected chlorophyll a fluorescence (ChlF) parameters in structured populations of Scots pine (Pinus sylvestris L.) grown on two sites under non-stress conditions. These parameters were derived from the OJIP part of the ChlF kinetics curve and characterize individual parts of primary photosynthetic processes associated, for example, with the exciton trapping by light-harvesting antennae, energy utilization in photosystem II (PSII) reaction centers (RCs) and its transfer further down the photosynthetic electron-transport chain. An additive relationship matrix was estimated based on pedigree reconstruction, utilizing a set of highly polymorphic single sequence repeat markers. Variance decomposition was conducted using the animal genetic evaluation mixed-linear model. The majority of ChlF parameters in the analyzed pine populations showed significant additive genetic variation. Statistically significant heritability estimates were obtained for most ChlF indices, with the exception of DI0/RC, φD0 and φP0 (Fv/Fm) parameters. Estimated heritabilities varied around the value of 0.15 with the maximal value of 0.23 in the ET0/RC parameter, which indicates electron-transport flux from QA to QB per PSII RC. No significant correlation was found between these indices and selected growth traits. Moreover, no genotype × environment interaction (G × E) was detected, i.e., no differences in genotypes' performance between sites. The absence of significant G × E in our study is interesting, given the relatively low heritability found for the majority of parameters analyzed. Therefore, we infer that polygenic variability of these indices is selectively neutral.
Keywords: Photosynthesis; Chlorophyll; Photosystem II Protein Complex; Trees; světlo; Forests; photosynthesis; lesy; stromy; Quantitative Trait, Heritable; chlorofyl; Genotype; zvířata; Photosynthetic Reaction Center Complex Proteins; Fluorescence; OJIP transient; Light; borovice lesní; genetická variace; Genetic Variation; fotosystém II (proteinový komplex); rostlinné geny; Pinus sylvestris; Genes, Plant; fotosyntetická reakční centra (proteinové komplexy); chlorofyl a; transport elektronů; Chlorophyll A; genotyp; fluorescence; Animals; fotosyntéza; Electron Transport; pedigree reconstruction; kvantitativní znak dědičný